Effect of Volatile Fatty Acids Accumulation on Biogas Production by Sludge-Feeding Thermophilic Anaerobic Digester and Predicting Process Parameters - Intisar Nasser Al-Sulaimi; Jagdeep Kumar Nayak; Halima Alhimali; Ahmed Sana; Abdullah Al-Mamun (Fermentation, 2022)
Sewage sludge represents an important resource for reuse in the wastewater treatment field. Hence, thermophilic anaerobic digestion (TAD) could be an alternative technique to recover renewable resources from sludge. In the TAD biodegradation process, volatile fatty acids (VFAs) are the intermediate products of methanogenesis. However, the higher formation and accumulation of VFAs leads to microbial stress, resulting in acidification and failure of the digester. Therefore, several batch TADs have been investigated to evaluate the VFAs production from sludge and their impact on biogas generation and biodegradation efficiency. Three types of sewage sludges, e.g., primary sludge (PS), secondary sludge (SS), and mixed sludge (MS) were used as substrates to estimate the accumulation of VFAs and yield of methane gas. The system showed the maximum total VFAs accumulation from both PS and MS as 824.68 ± 0.5 mg/L and 236.67 ± 0.5 mg/L, respectively. The dominant VFA accumulation was identified as acetic acid, the main intermediate by-product of methane production. The produced biogas from PS and MS contained 66.75 ± 0.5% and 52.29 ± 0.5% methane, respectively. The high content of methane with PS-feeding digesters was due to the higher accumulation of VFAs (i.e., 824.68 ± 0.5 mg/L) in the TAD. The study also predicted the design parameters of TAD process by fitting the lab-scale experimental data with the well-known first-order kinetic and logistic models. Such predicted design parameters are significantly important before the large-scale application of the TAD process.